Решение нормально разрешимых операторных уравнений в гильбертовом пространстве - Журавлев, В.Ф. (Нелінійні коливання, 2012)
Отримано формулу для єдиного псевдооберненого оператора до нормально розв’язного, умови iснування та зображення єдиного розв’язку нормально розв’язних рiвнянь у гiльбертових просторах. Введено поняття односторонньо псевдообернених операторiв до нормально розв’язних, якi дiють у гiльбертових просторах, розглянуто методи їх побудови. We find a formula for a unique pseudoinverse operator to a normally solvable equation in a Hilbert space, as well as existence conditions and a representation of a single solution of the equation. We also introduce the notion of an operator that is one-sided pseudoinverse of a normally solvable operator acting on a Hilbert space. Methods for constructing such operators are also considered.